2014
DOI: 10.1007/s12975-014-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Neural Network in Subarachnoid Hemorrhage

Abstract: This perspective article uses a new concept named vascular neural network as an umbrella to redefine vascular pathophysiology for subarachnoid hemorrhage (SAH) induced vasospasm and early/delayed brain injury. Five vascular components are discussed including large artery moderate vasospasm which may not contribute to reduced cerebral blood flow (CBF) and poor outcomes after SAH. Even severe vasospasm alone with lumen diameter narrowing less than 75% of the normal diameter may not cause delayed brain injury, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 53 publications
1
25
2
Order By: Relevance
“…A previous study indicated that MMP-9 was expressed in the vascular wall and the co-staining for vascular smooth muscle cells showed that the MMP-9 expression localized to the vascular smooth muscle cells after SAH 8 . The switch of vascular smooth muscle phenotype may not markedly affect the size or function of the large arteries in the previous study 1, 31 , but some studies reported that unbalanced contractile/synthetic vascular smooth muscle phenotype affected the size of the cerebral arteries and aggravated brain swelling and brain edema 29,30,32 . It is presumed that due to the limited two or three layers of smooth muscle cells in smaller arteries, vascular smooth muscle phenotype change causes the loss of small arteries vascular tone and affects BBB and autoregualtion.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A previous study indicated that MMP-9 was expressed in the vascular wall and the co-staining for vascular smooth muscle cells showed that the MMP-9 expression localized to the vascular smooth muscle cells after SAH 8 . The switch of vascular smooth muscle phenotype may not markedly affect the size or function of the large arteries in the previous study 1, 31 , but some studies reported that unbalanced contractile/synthetic vascular smooth muscle phenotype affected the size of the cerebral arteries and aggravated brain swelling and brain edema 29,30,32 . It is presumed that due to the limited two or three layers of smooth muscle cells in smaller arteries, vascular smooth muscle phenotype change causes the loss of small arteries vascular tone and affects BBB and autoregualtion.…”
Section: Discussionmentioning
confidence: 79%
“…The vascular neural network, which is an extended classical neurovascular unit, represents a new physiological unit to consider for therapeutic development in stroke 1, 3 . The vascular smooth muscle, as an important part of vascular neural network, might be an alternative therapy for early brain injury after SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is an important endogenous repair mechanism after brain injury, which may improve tissue perfusion, support the activity of neurons and neural progenitor cells, and collectively, promote long-term functional improvement [40-44]. The potent effect of DHA and FO combined treatment in promoting post-stroke neurogenesis suggests the potential development of new blood vessels, which provided a vascular niche that is required during neurogenesis [7].…”
Section: Resultsmentioning
confidence: 99%
“…The anterior choroidal artery, which lies proximal to the MCA and the end artery structure of humans contrasted to the more collateral structure of mice may offer clues as science develops improved biotechnology to traverse these diverse pathways. In TBI, the most common vascular injury is subarachnoid haemorrhage [10] with secondary vascular issues from vasospasm or lumen narrowing of arteries from edema or increased intracranial pressure that further reduce brain perfusion [11]. Vertebrobasilar dissection is more common than anterior dissection in traumatic brain injury.…”
Section: Translational Researchmentioning
confidence: 99%